Q: What is 9 yd 1 ft - 5 yd 2 ft?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3 ft = 1 yd → 5 ft = 1 yd 2 ft → 8 yd + 5 ft = 8 yd + 1 yd 2 ft = 9 yd 2 ft.

just subtract 5 yd by 1 yd then subtract 1ft by 2ft..... = 4yd's and 1 ft easy as pie but i hate pie.

192 inches in 5 yd 1 ft

1 yard = 3 feet 8 yards - 3 yards = 5 yards - 1 yard = 4 yards 3 ft + 1 ft - 2ft = 2 ft answer is 4 yards 2 feet

1 yd = 3 ft area = ½ × (sum bases) × height → area = ½ × (5 ft + 3½ yd) × 7 ft = ½ × (5 ft + (3½ × 3) ft) × 7 ft = ½ × (5 + 10½ ft) × 7 ft = 54¼ sq ft

Related questions

7 yd 1 ft - 5 yd 2 ft = 22 ft - 17 ft = 5 ft = 1 yd 2 ft.

2 yd 2 ft

3 ft = 1 yd → 5 ft = 1 yd 2 ft → 8 yd + 5 ft = 8 yd + 1 yd 2 ft = 9 yd 2 ft.

8 yds

The Answer is 2 yd 9 ft because its like 51-22=29

No. 1 yd = 3 ft → 2 yd = 6 ft > 5 ft.

just subtract 5 yd by 1 yd then subtract 1ft by 2ft..... = 4yd's and 1 ft easy as pie but i hate pie.

3 yd 2 ft - 1 ft 5 in = 9 ft + 2 ft - 1 ft - 5 in = 10 ft - 5 in = 9 ft 7 in = 3 yd 7 in

1

1 yd = 3 ft → 1 sq yd = 1 yd x 1 yd = 3 ft x 3 ft = 9 ft 1 yd = 36 in → volume = 4800 sq ft x 5 in = 4800 ÷ 9 sq yd x 5 ÷ 36 yd = 74 2/27 cu yd ≈ 74.074 cu yd.

8 yards 2 feet - 5 yards 1 foot = 3 yards 1 foot

Measurement of length. A foot is 12", a yard is 3 feet. 5 ft. = 1 yd., 2 ft.